2020
DOI: 10.1021/acs.cgd.0c01014
|View full text |Cite
|
Sign up to set email alerts
|

Ketoconazole: Solving the Poor Solubility via Cocrystal Formation with Phenolic Acids

Abstract: Ketoconazole (KTZ) is an imidazole derivative that is used to treat a wide variety of fungal infections and other human diseases. As a class II compound in the biopharmaceutics classification system, KTZ has low aqueous solubility. To improve this disadvantage, five phenolic acids were employed to form cocrystals with KTZ. The antifungal and anti-inflammatory activity of the phenolic acids may bring an enhanced therapeutic effect and reduce the risk of hepatotoxicity at the same time. The structural informatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 37 publications
(57 reference statements)
1
19
1
Order By: Relevance
“…Crystal structure of DPA_PA salt reveals the presence of a dimeric association between the protonated DPA molecule through the N-H•••O hydrogen bond like DPA alone with different symmetry operation (Table 2 and Figure 8a). There is no direct association between the PA¯-PA¯ anion ob- A similar phenomenon was also observed in the crystal structure of ketoconazole [57]. Interestingly, in the one configuration, the phenyl ring is roughly coplanar with chain moiety (excluding the iso-propyl moiety), whereas in other configuration, the 2-pyridine moiety is roughly coplanar with the chain moiety (excluding the iso-propyl moiety).…”
Section: Crystal Structure Of Dpa_pa Saltsupporting
confidence: 57%
“…Crystal structure of DPA_PA salt reveals the presence of a dimeric association between the protonated DPA molecule through the N-H•••O hydrogen bond like DPA alone with different symmetry operation (Table 2 and Figure 8a). There is no direct association between the PA¯-PA¯ anion ob- A similar phenomenon was also observed in the crystal structure of ketoconazole [57]. Interestingly, in the one configuration, the phenyl ring is roughly coplanar with chain moiety (excluding the iso-propyl moiety), whereas in other configuration, the 2-pyridine moiety is roughly coplanar with the chain moiety (excluding the iso-propyl moiety).…”
Section: Crystal Structure Of Dpa_pa Saltsupporting
confidence: 57%
“…During the past 20 years, cocrystallization has proved to be an effective approach to tailor physicochemical properties of active pharmaceutical ingredients (APIs) through reliable supramolecular synthons based on various hydrogen-bonding interactions. Solubility, dissolution, and bioavailability of APIs could be greatly enhanced by the formation of cocrystals. Moreover, pharmaceutical cocrystals could be endowed with superior humidity, thermal and photo stability. Recently, some pharmaceutical cocrystals showing potential extended release properties have been prepared, which indicated that cocrystallization could be a new strategy for achieving extended release of APIs. Like single APIs, however, polymorphism in pharmaceutical cocrystals is also quite common and the polymorphs of cocrystals can display significantly different properties. Therefore, polymorphism is an important consideration in the development of pharmaceutical cocrystals. In view of the fact that a high proportion of drugs are available in racemic form, the preparation of cocrystal polymorphs based on racemic APIs should be an important topic.…”
Section: Introductionmentioning
confidence: 99%
“…Of all the CCFs available, phenolic acids, because of their unique structure feature containing both hydroxyl and carboxyl groups on their benzene ring that can provide universal hydrogen-bonding sites, , have been viewed as the ideal candidate CCFs during the assembling of pharmaceutical cocrystals. Lately, some phenolic acids have been successfully cocrystallized with certain APIs for constructing pharmaceutical cocrystals, which has laid the foundation for the cocrystallization of phenolic acids with MLN. More importantly, a number of phenolic acids possessing excellent physicochemical properties can be used as natural nutraceuticals with potential health benefits, playing important roles in the human dietary and health protective.…”
Section: Introductionmentioning
confidence: 99%
“…From the perspective of practicality and medicinal function, the existing nutraceuticals among phenolic acids, except for healthcare, have been proven to have obvious biological and pharmacological effects in the antimicrobial, anticancer, and antiinflammatory, especially the spacious application prospect in the prevention and treatment of cardiovascular diseases with the low toxicity and reliable safety. , Therefore, in view of the unique superiority of phenolic acid nutraceuticals, they are significant as feasible CCFs in the pharmaceutical cocrystallization field. So far, although phenolic acid nutraceuticals as CCFs have been widely used in the amelioration of antibacterial and antitumor drugs via cocrystallization techniques, , there is almost nothing in the study of optimizing the properties and efficacy of cardiovascular drugs. According to these reasons, the design and preparation of MLN-phenolic acid nutraceutical cocrystals are of great significance to explore and evaluate the influence of phenolic acids with different substituents on in vivo/in vitro pharmaceutical performances of MLN, thus laying the application foundation for various phenolic acid nutrients in regulating and improving cardiovascular drugs by cocrystallization techniques.…”
Section: Introductionmentioning
confidence: 99%